Gender Difference in Response to Moral Dilemmas: An Experimental Study on Dual Process Theory of Moral Judgment - Husna, Sabiqotul (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2025)
Morality always becomes the basis for evaluating behavior in life regarding whatis acceptable and what is not. This study examined how gender and moral dilemma typeinfluence moral judgment (affirmative response, moral acceptability), emotional arousal,and valence in 60 Indonesian participants (30 female, 30 male; mean age = 22.45). Theresearch employed an experimental method using a factorial design and a vignette-basedscenario approach. Using a mixed factorial ANOVA, the results showed a significant maineffect of moral decision type on judgment, with deontological responses rated moreaffirmatively than utilitarian ones, where deontological judgments prioritize adherence tomoral rules or duties regardless of outcomes (e.g., refusing to harm one person even if itwould save many), while utilitarian judgments focus on the consequences of actions andaim to maximize overall well-being (e.g., endorsing harm to one if it leads to a greater good),(F(1, 56) = 13.74, p < .001, η2 = .197). Gender did not significantly affect moral acceptabilityor decision type, but females reported higher emotional arousal than males (F(1, 56) =5.93, p = .018, η2 = .096). Moral dilemma type significantly influenced both arousal (F(3,168) = 7.18, p < .001, η2 = .114) and acceptability (F(3, 168) = 10.24, p < .001, η2 = .154).Incidental harm was judged most acceptable, and elicited the highest arousal. Valenceratings were consistently negative across conditions, indicating the distressing nature ofmoral conflict. Theoretically, these findings support dual-process models of moralcognition, highlighting the dominant role of emotional arousal and contextual factors—particularly perceived intentionality and personal relevance—over stable individual traitslike gender. Practically, understanding how emotional and contextual variables shapemoral judgment can inform the development of ethics training and decision-makinginterventions in emotionally charged environments where professionals must often makemorally complex decisions under emotional pressure.